Nerve impulse transmission pathway-focused genes expression analysis in patients with primary hypothyroidism and autoimmune thyroiditis - Bilous, I. I.; Kord, M. M.; Krynytska, I. Y.; Kamyshnyi, A. M.; Камишний, Олександр Михайлович (My University, 2020)
Objective. Thyroid hormones have important actions in the adult brain. They regulate genes expression in myelination, differentiation of neuronal and glial cells, and neuronal viability and function. Methods. We used the pathway-specific real-time PCR array (Neurotrophins and Receptors RT2 Profiler PCR Array, QIAGEN, Germany) to identify and verify nerve impulse transmission pathway-focused genes expression in peripheral white blood cells of patients with postoperative hypothyroidism, hypothyroidism as a result of autoimmune thyroiditis (AIT) and AIT with elevated serum an anti-thyroglobulin (anti-Tg) and anti-thyroid peroxidase (anti-TPO) antibodies. Results. It was shown that patients with postoperative hypothyroidism and hypothyroidism resulting from AIT had significantly lower expression of BDNF and CBLN1. In patients with AIT with elevated serum anti-Tg and anti-TPO antibodies, the expression of GDNF was significantly down-regulated and the expression of PNOC was up-regulated. The expression levels of MEF2C and NTSR1 were decreased in the group of patients with postoperative hypothyroidism and AIT, correspondingly. Conclusions. The results of this study demonstrate that AIT and hypothyroidism can affect the expression of mRNA nerve impulse transmission genes in gene specific manner and that these changes in gene expressions can be playing a role in the development of neurological complications associated with thyroid pathology. Detection of the transcriptional activity of nerve impulse transmission genes in peripheral white blood cells can be used as an important minimally invasive prognostic marker of the risk for developing neurological complications comorbid with thyroid pathology.
Keywords: neurotrophin; mRNA; autoimmune thyroiditis; hypothyroidism